Sistem Kontrol Playlist Pada Radio Citis Fm Berbasis Android - Wahyudy, Dzulmy; Aswandi, Aswandi; Jamilah, Jamilah (Politeknik Negeri Lhokseumawe, 2022)
The development of science and technology cause humans always keep learning and looking for a way for the application of SCIENCE and TECHNOLOGY can provide many benefits and lighten the workload for humans. Development of communication media, especially broadcast media, i.e. radio and television is one of the most efficient forms of mass media in conveying information. Controlling playback of playlist on the radio it takes application of remote desktop technologies, to improve the quality of networks on the system as well as the application of the technology of the remote system to be built. The research aims to find out the quality of networks on the system using the method of QoS and the speed of response when the operator controlling using the remote on the system. In this study used QoS method as a parameter testing system. Data collected by doing a test run on a system that has been built. Testing done against delay, average – flat on a range of